Cardiac effects of acute exhaustive exercise in a rat model - Olah, Attila Josef; Németh, Balázs Tamás; Mátyás, Csaba; Horváth, Eszter Mária; Hidi, László; Birtalan, Ede; Kellermayer, Dalma; Ruppert, Mihály; Merkely, Gergő; Szabó, Gábor; Merkely, Béla; Radovits, Tamás (International journal of cardiology, 2015)
Background - The role of physical exercise in the prevention and treatment of cardiovascular diseases has been well described, however, elevations in cardionecrotic biomarkers after prolonged exercise (i.e. ultramarathon running) were observed. We aimed at understanding the biochemical, molecular biological, structural and functional alterations in the heart after exhaustive exercise in a rat model. - Methods - Rats of the exercise group were forced to swim for 3h with 5% body weight (workload) attached to the tail, control rats were taken into the water for 5min. After a 2-hour recovery period we performed left ventricular (LV) pressure-volume analysis to investigate LV function and mechanoenergetics. Additionally, blood and myocardium samples were harvested for biochemical and histological examinations. Gene expression changes were detected by qRT-PCR. - Results - When compared to controls, elevated plasma levels of cardiac troponin T and creatine kinase were detected after exhaustive exercise. Histological analysis showed sporadic fragmentation of myocardial structure and leukocyte infiltration in the exercised group. We observed increased end-systolic volume, decreased ejection fraction, impaired contractility (preload recruitable stroke work) and mechanoenergetics (ventriculoarterial coupling, mechanical efficiency) of LV after exercise. Myocardial expression of major antioxidant enzymes was increased along with increased myocardial nitro-oxidative stress. Bax/Bcl-2 ratio and TUNEL staining showed enhanced apoptotic signaling. Exhaustive exercise also resulted in the dysregulation of the matrix metalloproteinase system. - Conclusions - Excessive physical activity has an adverse effect on the heart. The observed functional impairment is associated with increased nitro-oxidative stress, enhanced apoptotic signaling and dysregulation of the matrix metalloproteinase system after exhaustive exercise.
Available online 23 December 2014
All of the authors take responsibility for all aspects of the reliability and freedom frombias of the data presented and their discussed interpretation
Gesehen am 23.06.2020